2022
DOI: 10.7557/3.6482
|View full text |Cite
|
Sign up to set email alerts
|

Needles in an ocean haystack: using environmental DNA to study marine mammals in the North Atlantic

Abstract: Marine mammals in the North Atlantic have experienced severe depletions due to overexploitation. While some species and populations have now recovered, there are numerous other anthropogenic activities impacting their North Atlantic ecosystem. Studying marine mammals is often associated with logistical challenges, and many species have an elusive nature, resulting in substantial knowledge gaps on the distribution, abundance and diversity of marine mammals in the North Atlantic. Environmental DNA (eDNA) is an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Initial applications of e-DNA collection methods focused on detecting species from among FIGURE 1 mixed samples in aquatic systems (Skinner et al, 2020). The presence of aquatic mammals has also been identified (Padgett-Stewart et al, 2016;Szeḱely et al, 2022). DNA has also been detected in paw-prints in snow (Daleń et al, 2007;Bellemain, 2017 unpublished report;Franklin et al, 2019;Hellström et al, 2019 unpublished report;Barber-Meyer et al, 2020;Barber-Meyer et al, 2022) and used to determine species presence.…”
Section: Introductionmentioning
confidence: 99%
“…Initial applications of e-DNA collection methods focused on detecting species from among FIGURE 1 mixed samples in aquatic systems (Skinner et al, 2020). The presence of aquatic mammals has also been identified (Padgett-Stewart et al, 2016;Szeḱely et al, 2022). DNA has also been detected in paw-prints in snow (Daleń et al, 2007;Bellemain, 2017 unpublished report;Franklin et al, 2019;Hellström et al, 2019 unpublished report;Barber-Meyer et al, 2020;Barber-Meyer et al, 2022) and used to determine species presence.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary metabarcoding studies have uncovered previously unknown marine mammal diets (Sonsthagen et al, 2020; Zhang et al, 2023), whilst eDNA metabarcoding has revealed spatiotemporal availability of prey species and detected co-occurrences between cetaceans and their prey (Djurhuus et al, 2020; Visser et al, 2021). However, few studies have harnessed eDNA to elucidate marine mammal trophic interactions to date (Székely et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in environmental DNA metabarcoding offer the opportunity to simultaneously monitor cetaceans and their prey, enabling long-term tracking of distributions, and to enhance our understanding of their dynamics (Székely et al, 2021). eDNA can expand the spatiotemporal scope of marine mammal monitoring where visual or acoustic monitoring are infeasible, i.e., at night or in adverse weather conditions and for cetaceans that vocalise infrequently or have unknown vocalisations (Baumgartner et al, 2019;Valsecchi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%